2015
DOI: 10.18517/ijaseit.5.5.567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying and Hydrodistillation Time on the Amount of Ginger Essential Oil

Abstract: The objective of this research is to study the effect of drying and hydrodistillation time on the amount of ginger (Zingiber officinale Rosc.) essential oil. For this purpose, a hydrodistillation laboratory-scale extraction unit was employed. The fresh ginger were dried by air drying for 1, 2 and 4 days at ambient temperature. In general, ginger oil obtained in the form of bright yellow liquid with a distinctive aroma of ginger. The experimental results showed that the yields of the ginger essential oils were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
6
0
2
Order By: Relevance
“…The chemicals content obtained in this study was similar to other published results although the highest major compound present was varied, in this study camphene whereas other reported curcumene [17,18]; zingiberene [20]; 1,8 cineol [21]. These suggest that chemical component obtained might also depend on the varieties or source of ginger material used as also observed by [13,14].…”
Section: Resultssupporting
confidence: 90%
“…The chemicals content obtained in this study was similar to other published results although the highest major compound present was varied, in this study camphene whereas other reported curcumene [17,18]; zingiberene [20]; 1,8 cineol [21]. These suggest that chemical component obtained might also depend on the varieties or source of ginger material used as also observed by [13,14].…”
Section: Resultssupporting
confidence: 90%
“…Decline in moisture content was observed with the drying time. The possible reason is that with increased drying time mass transfer also increases (Hasmita et al, 2015). However, this pattern of declining moisture content with drying time is only up to a defined limit because afterward, moisture content in food product dropped to a minimum value (Supardan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Then the temperature was gradually raised to start the distillation. Condenser was tap water cooled and the distillation was conducted for 4 h. Optimum hydro distillation time was found to be around 4 h or 240 min for 4 days dried ginger samples according to a recent Indonesian study ( Hasmita et al., 2015 ). Therefore, optimal parameters were used in the current study according to the requirement.…”
Section: Methodsmentioning
confidence: 99%